2014
DOI: 10.1021/es404390x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Binding Associated with Exposure to Fluorotelomer Alcohols (FTOHs) and Polyfluoroalkyl Phosphate Esters (PAPs) in Rats

Abstract: The biotransformation of fluorotelomer-based compounds such as fluorotelomer alcohols (FTOHs) and polyfluoroalkyl phosphate esters (PAPs) are sources of exposure to perfluorinated carboxylates (PFCAs), leading in part to the observation of significant concentrations of PFCAs in human blood. The biotransformation of FTOHs and PAPs yield intermediate metabolites that have been observed to covalently modify proteins. In the current investigation, the extent of covalent protein binding in Sprague-Dawley rats upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 45 publications
0
19
1
Order By: Relevance
“…1H-PFAs contain a labile hydrogen atom that may undergo further biotransformation. We will discuss possible metabolic end points of 1H-PFAs as they relate to literature information on 1H-perfluoroethane ( Harris et al 1992 ) and 8:2 fluorotelomer alcohol ( Martin et al 2009 ; Rand and Mabury 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1H-PFAs contain a labile hydrogen atom that may undergo further biotransformation. We will discuss possible metabolic end points of 1H-PFAs as they relate to literature information on 1H-perfluoroethane ( Harris et al 1992 ) and 8:2 fluorotelomer alcohol ( Martin et al 2009 ; Rand and Mabury 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, CYP 2E1 was reported to oxidize 8:2 fluorotelomer alcohol in rat hepatocytes, which provides evidence that compounds containing longer perfluoroalkyl chains can still undergo these oxidative reactions ( Martin et al 2009 ). The 8:2 fluorotelomer unsaturated aldehyde reacted to form both PFCAs and to covalently bind to proteins both in vitro ( Rand and Mabury 2013 ) and in vivo ( Rand and Mabury 2014 ). The longer-chained 1H-PFAs would likely have similarly slow reactivity to 1H-perfluoroethane to form PFCAs or other biological nucleophiles such as certain amino acids in proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although persistent PFCAs, PFSAs and PFPiAs would not undergo biotransformation in biological systems, some of the precursor PFSAs and PFCAs can as well as PFPiAs. Some conjugated products, such as FTOH-sulfate, FTOH-glucuronide and different FTUCA-glutathione (GSH) conjugates that have been observed in animal exposure of PFCA precursors (e.g., diPAP or FTOH) (Rand and Mabury, 2014), were not measured in current investigation. The detection of some intermediates such as 5:3 and 7:3 FTCAs in the samples suggested the biotransformation of FTOH in the biological system.…”
Section: Eofmentioning
confidence: 99%
“…54 An in vivo study also found protein adducts in the plasma, liver, and kidney of rats administered with 8:2 FTOH or 6:2 polyuoroalkyl phosphate diester (6:2 diPAP). 55 Rand et al 56 demonstrated that binding of 8:2 FTUAL to proteins might be the primary fate in the biotransformation of 8:2 FTOH. Covalent binding of FTUAL with proteins could affect protein functions and thereby induce serious toxic effects.…”
Section: Phase II Metabolism Of 8:2 Ftohmentioning
confidence: 99%